Limitations to the Implied Powers of International Organizations - Gadkowski, Andrzej (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2022)
The aim of this article is to present the main aspects of limitations to the implied powers of international organizations. The author discusses the most important case law and the position on this topic presented, in particular, by the International Court of Justice. He points to the most salient categories in the catalogue of the limits of implied powers of international organizations.